2011
DOI: 10.1371/journal.pntd.0001383
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CD4+CD25+FOXP3+ Regulatory T Cells during Human Hookworm Infection Modulates Antigen-Mediated Lymphocyte Proliferation

Abstract: Hookworm infection is considered one of the most important poverty-promoting neglected tropical diseases, infecting 576 to 740 million people worldwide, especially in the tropics and subtropics. These blood-feeding nematodes have a remarkable ability to downmodulate the host immune response, protecting themselves from elimination and minimizing severe host pathology. While several mechanisms may be involved in the immunomodulation by parasitic infection, experimental evidences have pointed toward the possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 70 publications
6
46
1
1
Order By: Relevance
“…Nevertheless, it was found that hookworm-infected individuals display higher proportions of circulating CD4 ϩ CD25 ϩ Foxp3 ϩ Tregs than uninfected controls (233). In addition, among patients with intestinal nematode infections, in vitro T cell responses to malaria and mycobacterial antigens were depressed but were rescued following Treg depletion (296).…”
Section: Regulatory Cell Populations In Human Infectionmentioning
confidence: 99%
“…Nevertheless, it was found that hookworm-infected individuals display higher proportions of circulating CD4 ϩ CD25 ϩ Foxp3 ϩ Tregs than uninfected controls (233). In addition, among patients with intestinal nematode infections, in vitro T cell responses to malaria and mycobacterial antigens were depressed but were rescued following Treg depletion (296).…”
Section: Regulatory Cell Populations In Human Infectionmentioning
confidence: 99%
“…+ regulatory T cells [23] and repeated infection with hookworm stimulates production of high levels of IL-10 [24], which inhibits host protective immunity against M. tuberculosis. Accordingly, there is a possibility that hookworm-induced IL-10 impacts on the sensibility to M. tuberculosis infection.…”
Section: Il-10mentioning
confidence: 99%
“…These cells are able to control both Th2 and Th1 type immune responses [17]. Helminth infection can increase the frequency of Treg cells in mice [18,19], and in man an increase of Treg cells has been observed in Strongyloides infection in patients coinfected with HTLV-1 [20] as well as in hookworm-infected patients [21]. Furthermore, it has been shown that Treg cells can modulate the immune response in Mycobacterium bovis bacille Calmette-Guerin (BCG)-vaccinated individuals [22,23] and in patients with active TB [24].…”
Section: Introductionmentioning
confidence: 99%